2020
DOI: 10.3389/fimmu.2020.584303
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptors: Regulators of Cholesterol Metabolism, Inflammation, Autoimmunity, and Cancer

Abstract: The interplay between cellular stress and immune response can be variable and sometimes contradictory. The mechanisms by which stress-activated pathways regulate the inflammatory response to a pathogen, in autoimmunity or during cancer progression remain unclear in many aspects, despite our recent knowledge of the signalling and transcriptional pathways involved in these diseases. In this context, over the last decade many studies demonstrated that cholesterol metabolism is an important checkpoint for immune h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 110 publications
0
61
0
2
Order By: Relevance
“…LXRα is highly expressed in adipose tissue, liver, adrenal glands, lungs, and gastrointestinal tract, while LXRβ is widely expressed (Repa and Mangelsdorf 2000 ). Upon activation by ligands, LXRs heterodimerize with retinoid X receptors (RXRs) and bind to target gene promoters, resulting in the regulation of various cellular parameters such as cholesterol synthesis and transport, glucose homeostasis, inflammatory, and immune responses (Bilotta et al 2020 ; Lin and Gustafsson 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…LXRα is highly expressed in adipose tissue, liver, adrenal glands, lungs, and gastrointestinal tract, while LXRβ is widely expressed (Repa and Mangelsdorf 2000 ). Upon activation by ligands, LXRs heterodimerize with retinoid X receptors (RXRs) and bind to target gene promoters, resulting in the regulation of various cellular parameters such as cholesterol synthesis and transport, glucose homeostasis, inflammatory, and immune responses (Bilotta et al 2020 ; Lin and Gustafsson 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the anti-inflammatory or proinflammatory role of LXR still remains controversial. Function of these NRs are various depending on the different cell types and disease context ( 25 ). With regard to myeloid differentiation, it has been shown that overexpression of LXRα promoted maturation of DCs and endowed it with enhanced ability to stimulate T-cell proliferation ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also a link between cholesterol metabolism and the inflammatory response. The transcription factor Liver-xreceptor regulates cholesterol metabolism and the inflammatory response (Bilotta et al, 2020). Moreover, the sterol metabolite 25hydroxycholesterol modulates the inflammatory response (Gold et al, 2014).…”
Section: Alteration In Cholesterol Metabolism In Response To Telencephalon Injurymentioning
confidence: 99%